Attitudes towards distance Learning in Morocco within Covid 19: Public High School Teachers and Students as a Case Study (Global Journal of Human-Social Science, 2022)
This study investigates Moroccan EFL Students and teachers attitudes towards distance learning The study tackles students learning using Miscrosoft teams their knowledge about the platform and the efficiency of this new teaching tool to satisfy their learning needs The enquiry exerts a quantitative method using a questionnaire to collect data The questionnaire was administered to Ibnu Elhaytham High school teachers and students Kenitra
Keywords: students’ attitudes; teachers’ attitudes; platforms; microsoft teams; EFL context; learning needs; training; online courses